The Influence of Digital Marketing and Electronic Word of Mouth on Customer Retention in Generation Z Consumers in TikTok Shop with Brand Trust as a Moderator - Farhah, Nabilla Fitri Assy; Reza, Bobby; Kamaruddin, Muhammad Junaid (SAFE-Network, 2026)
This study was conducted in response to the growing phenomenon in which digital marketing gradually replaces traditional marketing, with TikTok shop exemplifying expertise in sustaining social commerce amid intense competition. The research aims to examine the influence of Digital Marketing (X1) and Electronic Word of Mouth (X2) on Customer Retention (Y), with Brand Trust (Z) positioned as a moderating variable. A quantitative approach was employed using Structural Equation Modeling (SEM) with SmartPLS software, as this method is suitable for testing complex relationships among latent constructs. Data were collected through surveys distributed to Generation Z consumers actively engaged with TikTok shop, ensuring representation of the population most immersed in social commerce. Measurement indicators included promotional strategies, SEO, social media, public relations, e-WOM intensity, valence, content, and trust dimensions. The findings revealed that Digital Marketing and Brand Trust significantly and positively affect Customer Retention, while the moderating role of Brand Trust was not statistically significant. These results imply that effective digital marketing strategies and trust-building initiatives are crucial for sustaining customer loyalty, though trust alone may not strengthen moderating effects.